A brief review on free light chain assays: from conventional to current - Zahari Sham, Siti Yazmin; Chellappah Thambiah, Subashini; Samsudin, Intan Nureslyna (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Free light chains (FLCs) are tumour markers of monoclonal gammopathies. Detection of urinary FLC or also known as Bence-Jones protein through urinary protein and its immunofixation electrophoreses (UPE and uIFE, respectively) have been considered the gold standard for its biochemical diagnosis. This is mainly due to their superior detection limits compared to their counterpart investigations in serum. However, urinalysis is limited in many ways. The emergence of serum FLC assay with markedly improved detection limit circumvents many of these problems and has gained much importance in biochemical investigations of monoclonal gammopathies. Nevertheless, they are not without limitations. This review discusses the advantages and limitations of serum and urinary FLC assays.